Analysis of Production Factors that Influence the Production of Red Chili Farming in Taraju District, Tasikmalaya Regency - Candra Nuraini; Abdul Mutolib; Octaviana Helbawanti; Januar A Ruslan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This aims to analyze the factors used in red chili farming activities and the factors that influence red chili production in Banyuasih Village, Taraju District, Tasikmalaya Regency. Research method with a survey approach. The research was conducted in Banyuasih Village, Taraju District, Tasikmalaya Regency—location determination technique using purposive sampling. The essential consideration is that this location is a red chili center. The data used are primary and secondary. The population in this study were sizeable red chili farmers in Banyuasih Village, totaling 210 farmers and members of 6 farmer groups. So that the determination of respondents or research samples is carried out using proportional random sampling. The analytical method used to determine the influence of production factors on production uses a regression equation with the Cobb-Douglas function model and classical assumption testing with Eviews software. Overall (simultaneously) production factor variables: seeds (X1), land area (X2), labor (X3), Urea (X4), Phonska (X5), compost (X6), KCL Fertilizer (X7), Manure ( X8), Insecticide (X9), Herbicide (X10), Fungicide (X11), Dolomite (X12) simultaneously influence red chili production at a 95% confidence level. According to the results of the t-test analysis, the variables that had a significant effect were seeds, labor, and phosca. Meanwhile, the variables of land area, compost, KCl fertilizer, urea fertilizer, manure, insecticides, herbicides, fungicides, and dolomite had no significant effect on red chili production.